Therapeutic Drug Monitoring (TDM): A Necessity in Critical Care and Transplant Settings - Agrawal, Rashmi (Indian Journal of Pharmacy & Drug Studies, 2025)
Therapeutic drug monitoring (TDM) personalizes dosage by quantifying plasma concentrations to enhance treatment effectiveness and reduce toxicity. In critically sick patients and transplant recipients, pathophysiological alterations, restricted therapeutic indices, and organ support measures frequently result in unexpected pharmacokinetics (PK). This study emphasizes TDM's significance in critical care and transplantation, concentrating on antimicrobials such as vancomycin, β-lactams, antifungals, and immunosuppressants like tacrolimus, cyclosporine, and mycophenolic acid, substantiated by PubMed-cited literature.